LINC01615 activates ZEB2 through competitively binding with miR-3653-3p to promote the carcinogenesis of colon cancer cells. Issue 3 (1st February 2022) - Hu, Zhen; Yang, Chong; Guo, Shangqi; Li, Yiqun; Li, Yaoping
ABSTRACT: As a newly discovered cancer-related molecule, we explored the unreported mechanism of LINC01615 intervention in colon cancer. LINC01615 expression in clinical samples and cells were detected. Effects of LINC01615 silencing/overexpression on the malignant development of colon cancer cells were analyzed through cell function experiments. Changes at the level of molecular biology were detected by quantitative real-time polymerase chain reaction and Western blot. Bioinformatics analysis and dual luciferase reporter assay were involved in the display and verification of targeted binding sequences. The rescue tests and correlation analysis examined the relationship among LINC01615, miR-3653-3p and zinc finger E-box binding homeobox 2 (ZEB2) in colon cancer cells. The xenograft experiment and immunohistochemistry were performed to verify these results. TCGA suggested that LINC01615 was high-expressed in colon cancer, as verified in clinical and cell samples, and patients with LINC01615 overexpression suffered from a poor prognosis. Silent LINC01615 blocked the malignant development of colon cancer cells through regulating related genes expressions, while overexpressed LINC01615 had the opposite effect. LINC01615, which was targeted by miR-3653-3p, partially offset the inhibitory effect of miR-3653-3p on colon cancer cells. The downstream target gene ZEB2 of miR-3653-3p was high-expressed in colon cancer. MiR-3653-3p was negatively correlated with LINC01615 or ZEB2, while LINC01615 was positively correlated with ZEB2. Therefore, LINC01615 induced ZEB2 up-regulation, while miR-3653-3p reduced ZEB2 level. The results of in vivo studies were consistent with cell experiments. LINC01615 competitively binds with miR-3653-3p to regulate ZEB2 and promote canceration of colon cancer cells.